Enabling live video technology for distance learning using IP based camera / Nor Syuhaila Sobri - Sobri, Nor Syuhaila (2007)
Most university in Malaysia is still using the traditional learning method in order to deliver the education to their students. They does not realized by applying e-learning concept will give more benefits to both lecturer and students. Therefore, we proposed the distance learning environment to change perception about e-learning education system. The used of video in teaching and learning will play a bigger role in delivery course materials to student. In order to enable live video technology, IP camera had been chosen. Before proposing the documentation, we have to identify the user requirement in this project. This elicitation is used the scenario-based technique to identify the requirement. We also proposed algorithm of bandwidth detection in order to detect the bandwidth of a current network. The recommendation to which video is most suitable depends on the bandwidth.